An improved virtual material based acoustic model for contact stiffness measurement of rough interface using ultrasound technique. (15th December 2018) - Xiao, Huifang; Sun, Yunyun
Abstract: In this work, an improved acoustic model based on virtual material is proposed to provide an accurate measurement of interfacial contact stiffness using ultrasound. The rough interface is assumed to be a thin layer of virtual material to incorporate the effect of ultrasound attenuation at the interface. The derived acoustic model shows that the developed contact stiffness expression is a refinement of the general spring model by considering the interfacial property and is related to the material properties of the virtual material thin layer. The analytical solutions of the material parameters for the virtual material are further deduced based on the statistical micro-contact theory. It reveals that the surface roughness parameters of the contact interface and the material property of the contact body are other information required to improve the measurement accuracy of contact stiffness, in addition to the ultrasonic measurement parameters in the original spring model. The accuracy of the developed acoustic model for contact stiffness measurement is verified by comparison with the spring model and the statistical contact models.